Insider Movement Ditinjau dari Eklesiologi HKBP - Cindi Oktaviani Manik (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study examines the phenomenon of Insider Movement in Tanggul Subdistrict, Jember Regency, East Java, from the perspective of the ecclesiology of the Huria Kristen Batak Protestan Church (HKBP). The Insider Movement is a phenomenon in which individuals from non-Christian religious backgrounds profess faith in Jesus Christ while remaining within their original socio-religious communities. This research aims to analyze the characteristics of the faith practices of the Insider community in Tanggul and to formulate an ecclesiological stance for HKBP regarding this phenomenon. The research method employs a qualitative approach with a theological-reflective research type, utilizing literature study, semi-structured interviews, and field observation. The findings indicate that the Insider community in Tanggul falls within the C4-C5 spectrum of Travis's C-Spectrum framework, characterized by following Jesus and the Bible, fellowship led by indigenous believers, spiritual transformation, remaining as witnesses within their original communities, and early-stage multiplication that remains limited. The study identifies both points of encounter and tension between the Insider Movement phenomenon and HKBP ecclesiology, particularly concerning the three marks of the true church (Notae Ecclesiae): pure preaching of the Word, rightful administration of the sacraments, and responsible church discipline. The implications of this research emphasize the need for a constructive ecclesiological stance that balances faithfulness to church identity with sensitivity to social context, along with pastoral accompaniment oriented toward the growth of complete faith leading toward the visible communion of the church.